Obstacles to Development of Entrepreneurship in Pakistan - Noor Alam; Jovan Shopovski; Aicha El Alaoui (European Scientific Journal, ESJ, 2024)
This paper aims to examine the obstacles to entrepreneurship in Pakistan. The study has adopted a qualitative and quantitative approach through descriptive approach. It conducted in-depth interviews and group discussions with mid and senior-level managements of SMEs and non-SMEs, as well as think tanks and students from relevant disciplines. Chi-square and Mann-Whitney U tests were followed by using Likert Scales for robustness in findings. A questionnaire was sent through e-mail to 150 Small or Medium Size Enterprises, SMEs, and 204 non-SMEs. 83 responses from SMEs and 135 responses from non-SMEs were obtained. The results show that the obstacles to entrepreneurship in Pakistan are multiple. Political instability, a deficient legal system, red tape-filled bureaucracy, and access to funding were registered as the main obstacles to entrepreneurship in Pakistan. The study recommends that the government adopt long-term objectives and strategies for SMEs and take a proactive stance.